Opportunities and Challenges of Rehabilitation of Degraded Land in the Case of Offa Woreda, Wolaita Zone, Ethiopia - Elias Bojago (Zien Journals, 2021)
In Ethiopia, land degradation has become a serious problem affecting all spheres of the social, economic and political life of the population. It is one of the major challenges to the agricultural development and food security of the country. In order to solve the problem of land degradation, a lot of efforts have been made since the 1970s. This research was conducted in the Case of Offa Woreda selected kebeles. The major purpose of this study was to assess opportunities and challenges of degraded land rehabilitation and the specific objectives of this research were to identify major opportunities and challenges of degraded land rehabilitation in the study area. The study was undertaken in Offa Woreda selected kebeles in the SNNPR region. In the study area the number of total households would be are 2155 and of the total 9% (82) was selected for this research study in order to achieve the objective of the study was gather, For this study both primary and secondary data was generated. The primary data collection was started with a preliminary survey followed by a key informant interview, focus group discussions, and a household survey with questionnaires. The collected data was analyzed using descriptive statistics. The quantitative data were analyzed using frequency and percentage when appropriate. The qualitative data was discussed to substantiate the study. And the results were expressed in the form of tables and graphs. The findings of the study indicated that limited labour availability, high cost of maintenance. Lack of knowledge, topography, soil conditions, high rainfall, high surfaces runoff, poor vegetation coverage, poor monitoring and evaluation, poor implementation and poor training on the technology use are major challenges encountering the land rehabilitation practices in an effective way.
Keywords: Land Rehabilitation; Land Degradation; Challenges; Opportunities